A short review of environmentally friendly spacer coatings to minimize membrane fouling - Tan, Jia Xin; Foo, Kathleen; Liang, Y. Y. (Trans Tech Publications, Switzerland, 2025)
Desalination plays a crucial role in addressing global water scarcity by providing a reliable source of freshwater from seawater and brackish water, supporting both human consumption and industrial needs. Feed spacers are an essential component of membrane systems, enhancing mixing and mass transfer. However, they also facilitate foulant deposition, with biofouling often initiating on the spacer surface before spreading to the membrane. Biofouling poses a significant challenge as it is difficult to remove once occurred. In response, extensive research has explored modifying feed spacer surfaces to mitigate fouling. Despite advancements, the use of hazardous chemical reagents in conventional spacer coatings raises serious environmental concerns, including contamination of the food chain and potential risks to human health. This review focuses on eco-friendly spacer coating strategies for biofouling resistance, emphasizing sustainable methods to address the environmental impacts of traditional approaches. Techniques such as plasma pretreatment, direct coating, oil-infused coatings, and candle-soot coatings have shown potential in reducing biofouling by modifying surface properties, including hydrophilicity, hydrophobicity, and biocidal characteristics. These methods have proven effective in mitigating membrane fouling, thereby improving the performance and lifespan of membrane systems. Finally, the paper outlines future research directions, including experimental and numerical approaches, to enhance spacer coatings for antifouling in membrane applications.